2002
DOI: 10.4141/a01-082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lighting on ground beef acceptability

Abstract: Barbut, S. 2002. Effect of lighting on ground beef acceptability. Can. J. Anim. Sci. 82: 305-309. The effects of incandescent (INC), cool-white fluorescent (FL), and metal halide (MH) light sources on the appearance of medium, lean, and extra lean ground beef meat were investigated. Meat color with INC illumination was preferred (P < 0.05) over that with MH illumination for all meat types, and over FL illumination for extra-lean and medium meats. The majority of the panelists described the meat as red under IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…There were significant differences between FLS and PPLED treatments throughout the 9 d storage period. These results are consistent with those reported by Lentz (1971) and Barbut (2002) who reported that the panelists found dark red or brown color of ground beef under FLS lighting. In addition, Bertelson and Skibsted (1987) indicated that the beef retains an acceptable color under LED light for 3 days.…”
Section: Sensory Analysissupporting
confidence: 93%
“…There were significant differences between FLS and PPLED treatments throughout the 9 d storage period. These results are consistent with those reported by Lentz (1971) and Barbut (2002) who reported that the panelists found dark red or brown color of ground beef under FLS lighting. In addition, Bertelson and Skibsted (1987) indicated that the beef retains an acceptable color under LED light for 3 days.…”
Section: Sensory Analysissupporting
confidence: 93%
“…(1992) for low fat ground beef (Hunter values: 37.1, 12.1 and 10.6, respectively). The spectra curve of the control was similar to lean beef reflectance spectra published by Swatland (1989a), and by Barbut (2002b). The addition of nitrite resulted in the formation of nitrosomyoglobin, which is less bright red compared with the oxymyoglobin pigment (Aberle et al.…”
Section: Resultssupporting
confidence: 71%